A robust affine projection sign algorithm against the high power of measurement noises. (20th May 2016) - Yoo, JinWoo; Shin, JaeWook; Song, Insun; Park, P.
Summary: This paper proposes a novel robust affine projection sign algorithm (R‐APSA) through a modified criterion that consists of the Euclidean norm of the sum of the difference between the present weight vector and the previous weight vectors. Because the filter update equation of the proposed R‐APSA is obtained from the modified criterion, it has robustness against the high power of measurement noises. Moreover, due to the characteristic inherent in the original APSA, the proposed R‐APSA performs well even though impulsive noises occur. Simulation results verify that the proposed R‐APSA attains smaller steady‐state errors than the existing released algorithms. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Proposed is a novel robust affine projection sign algorithm (R‐APSA) through a modified criterion that consists of the Euclidean norm of the sum of the difference between the present weight vector and the previous weight vectors. Because the update equation of the proposed R‐APSA is obtained from the modified criterion, it has robustness against the high power of measurement noises. Because of the characteristic inherent in the original APSA, the proposed R‐APSA performs well even though impulsive noises occur.